Biochar marine anticorrosive water-based paint and preparation method thereof
By adding biochar and water-based resin to water-based paint, a marine anti-corrosion water-based paint that is both environmentally friendly and corrosion-resistant is prepared, which solves the problems of insufficient durability and mechanical properties of water-based paint in the marine environment and achieves efficient anti-corrosion effect.
Patent Information
- Application Number
- CN202511057808.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-10-17
AI Technical Summary
Existing water-based coatings have poor durability in marine environments, are prone to aging, have poor mechanical properties and are expensive, making it difficult to meet the protection needs of marine concrete.
Biochar is used as a filler and combined with water-based epoxy resin, water-based polyurethane or water-based acrylic resin to prepare biochar marine anti-corrosion water-based coating through a specific process to optimize the hydrophobicity, density and flexibility of the coating.
The corrosion resistance and mechanical properties of the coating are improved, the porosity is reduced, the hydrophobicity is enhanced, and the coating has anti-freeze, anti-dyeing and anti-ultraviolet functions. The raw materials are cheap and easily available and the preparation process is simple.
Smart Images

Figure CN120795739A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a kind of anticorrosive coating and its preparation method, especially a kind of biochar marine anticorrosive water-based paint and its preparation method. BACKGROUND
[0002] Reinforced concrete structure is widely used, however, in the complex marine environment of high humidity, high salt fog, its durability is greatly challenged. Environmental factors exacerbate the deterioration of reinforced concrete performance, seriously affect its structural integrity and service life. At present, there are many improvement measures, among which, surface coating protection has the advantages of low cost, simple construction and is suitable for new and old projects. And developing high-performance and environmentally friendly new coatings has become a development trend.
[0003] According to the different dispersion medium, the commonly used coating system can be divided into traditional oil-based paint and water-based paint, water-based paint is gradually replacing traditional paint due to its low VOC (volatile organic compounds) emission, non-toxic, environmental protection and other advantages. However, water-based coating is rarely used for the protection of marine concrete, the main reason is that the durability of water-based coating in seawater environment is extremely high, and the traditional water-based coating is easy to age, has poor mechanical properties, high cost and poor corrosion resistance. Although water-based coating has potential application value in marine concrete under the trend of environmental protection, its application still faces a series of problems. The addition of fillers in water-based paint can improve it to a certain extent.
[0004] Biochar has been used as a filler for coating due to its advantages of abundant raw materials, low cost, negative carbon, stable physicochemical properties, rich pore structure, large specific surface area and other advantages. With the increase of the proportion of biochar incorporated into water-based paint, the compactness of the coating is reduced, but the hydrophobicity is improved to a certain extent. The larger the water contact angle of the coating, the higher the hydrophobicity, which can reduce the wetting and penetration of water on the surface of the concrete, thereby reducing the penetration speed of corrosion media such as chloride ions and sulfate. The higher the compactness of the coating, the more it can directly block the penetration of chloride ions and water, but the water-based coating with excessive compactness has poor flexibility and high brittleness. Therefore, the corrosion resistance of the coating is the result of the balance of hydrophobicity, compactness, durability and other factors.
[0005] The biochar coating reported at present all adds hydrophobic reagent or combines with other fillers (such as nanoparticles, hydrophobic particles, etc.), and has the problem of complex formula. SUMMARY
[0006] The purpose of the present application is to provide a biochar marine anticorrosive water-based paint with environmental protection and corrosion resistance;
[0007] The second purpose of the present application is to provide a preparation method of the above-mentioned biochar marine anticorrosive water-based paint.
[0008] Technical solution: The biochar marine anticorrosive water-based paint provided by the application comprises component A and component B; the component A comprises, in terms of mass fraction, 10-40 parts of biochar, 24-72 parts of water-based epoxy resin, and 0.1-0.4 parts of dispersant; the component B comprises, in terms of mass fraction, 6-18 parts of curing agent, 0.15-0.6 parts of water-based defoaming agent, 0.25-1 part of thickening agent, 0.1-0.4 parts of coupling agent, and 0.05-0.2 parts of drying agent.
[0009] The component A further comprises water-based polyurethane and / or water-based acrylic resin. The addition of the water-based epoxy resin and the water-based polyurethane or acrylic resin can reduce the cost, balance the problem that the water-based epoxy resin is relatively thin and the water-based polyurethane is too thick, and improve the flexibility and compactness of the prepared coating compared with a single resin coating.
[0010] The mass ratio of the water-based epoxy resin to the water-based polyurethane or water-based acrylic resin is 1:1-2:1, and the mass ratio of the water-based epoxy resin to the sum of the mass of the water-based polyurethane and the mass of the water-based acrylic resin is 1:1-2:1.
[0011] The biochar is derived from one of wheat, corn, rice and wood, and the particle size of the biochar is about 75 μm.
[0012] The dispersant is preferably a polycarboxylic acid sodium salt type dispersant, more preferably a dispersant with a product model number of SN-5040; the curing agent is preferably a water-soluble epoxy curing agent of a polyamide type, more preferably a curing agent with a product model number of F0705; the water-based defoaming agent is preferably a non-ionic water-based defoaming agent, more preferably a water-based defoaming agent with a product model number of J0413; the thickening agent is preferably a polyether type polyurethane water-based emulsion thickening agent, more preferably a thickening agent with a product model number of 2521; the coupling agent is preferably an epoxy group functional silane coupling agent, more preferably KH-560; and the drying agent is preferably a water-based composite type cobalt-free drying agent, more preferably a drying agent with a product model number of J2503.
[0013] The above biochar marine anticorrosive water-based paint preparation method comprises the following steps:
[0014] (1) mixing biochar, water-based epoxy resin, dispersant, curing agent and water-based defoaming agent, and ultrasonic dispersion;
[0015] (2) adding a coupling agent to step (1) to obtain a paint solution;
[0016] (3) ultrasonic dispersion and defoaming treatment of the paint solution;
[0017] (4) adding a thickening agent and a drying agent to step (3) and stirring uniformly to obtain the biochar marine anticorrosive water-based paint.
[0018] In step (3), the temperature of ultrasonic dispersion is 35-45℃. Changing the temperature of ultrasonic, when the temperature is 35-45℃, the increase of temperature will enhance the ability of molecular movement, promote the hydrophilic components (such as surfactants or polar groups) to migrate to the surface of the coating, and during the rapid evaporation of the solvent, the hydrophilic components are locked on the surface to form an enrichment layer, while the hydrophobic components sink to the inside. Due to the limitation of solvent evaporation path, the interface effect may lead to the formation of hydrophobic structure on the back side which is in contact with the substrate.
[0019] In step (1), the biochar is mixed with the water-based epoxy resin, and then the dispersant, the curing agent, and the water-based defoaming agent are added in sequence.
[0020] Alternatively, the water-based epoxy resin is mixed with the curing agent, the defoaming agent is added, ultrasonic dispersion is performed, and then the biochar and the dispersant are added in sequence.
[0021] Alternatively, the curing agent is diluted, mixed with the biochar, and then the dispersant is added and ultrasonic dispersion is performed, and then the water-based epoxy resin is added and stirred.
[0022] Changing the order of adding the water-based epoxy resin, the biochar, and the curing agent can optimize the performance of the coating. The water-based epoxy resin is first mixed with the biochar, the water-based epoxy resin enters the pores of the biochar, the filler is preferentially dispersed in the uncured epoxy emulsion, and the epoxy serves as the continuous phase to wet the surface of the filler. After the curing agent is added, the crosslinking reaction coats the filler in a three-dimensional network, forming a strong interfacial bond. The water-based epoxy resin is first mixed with the curing agent to form a crosslinked network, the viscosity of the coating increases, and the biochar filler added later is not easy to deposit and is more uniformly dispersed. The diluted curing agent is mixed with the biochar, and because the viscosity of the curing agent is too high, it is easy to agglomerate and difficult to mix when directly mixed with the biochar. After dilution, the viscosity of the curing agent is reduced, the filler preferentially contacts the curing agent, and the biochar surface is coated with the curing agent, making the biochar itself sticky. The subsequent addition of epoxy initiates crosslinking, and the filler is distributed at the curing agent-epoxy interface.
[0023] In step (1), the biomass is carbonized at a temperature of 400-500℃ to obtain the biochar.
[0024] The above-mentioned preparation method of the biochar marine anti-corrosion water-based coating comprises the following steps:
[0025] (1) Mix the biochar, the water-based epoxy resin, the water-based polyurethane and / or the water-based acrylic resin, the dispersant, the water-based defoaming agent, and the coupling agent, and perform ultrasonic dispersion;
[0026] (2) Add the curing agent to step (1) and perform degassing treatment to defoam;
[0027] (3) adding thickening agent, drying accelerator to step (2) and stirring evenly, to obtain the biochar marine anticorrosive water-based paint.
[0028] In step (1), the biochar is mixed with the water-based epoxy resin and stirred, and then the water-based polyurethane and / or water-based acrylic resin, water-based defoaming agent, coupling agent are added in sequence;
[0029] Alternatively, the biochar is mixed with the water-based polyurethane and / or water-based acrylic resin and stirred, and then the water-based epoxy resin, water-based defoaming agent, coupling agent are added in sequence;
[0030] Alternatively, the water-based epoxy resin is mixed with the water-based polyurethane and / or water-based acrylic resin and stirred, and then the biochar, defoaming agent, and dispersant are added in sequence; the water-based defoaming agent and coupling agent are added after the curing agent in step (2).
[0031] Advantages: Compared with the prior art, the present application has the following remarkable effects: (1) The microstructure of the biochar in the paint of the present application is porous, and the water-based polymer resin penetrates into these pore structures and interacts with the biochar, and the small particles of the biochar fill the gaps of the base paint, reducing the porosity and cracking possibility of the coating, thus the addition of the biochar is economic and environmentally friendly, can reduce the porosity of the coating, and improve the corrosion resistance of the coating. (2) The paint of the present application not only can improve the mechanical properties of the coating and improve the corrosion resistance, but also can endow the coating with some functionality, such as hydrophobicity, anti-freezing, stain resistance, and anti-ultraviolet radiation, etc. (3) The raw materials used are cheap and easy to obtain, the preparation process and composition are simple, and the corrosion resistance is excellent. BRIEF DESCRIPTION OF DRAWINGS
[0032] Figure 1 Preparation flow chart of the biochar marine anticorrosive water-based paint prepared in Example 1 of the present application;
[0033] Figure 2 Physical picture of the biochar paint of Example 1 and Example 3 of the present application;
[0034] Figure 3 Physical picture of the water-based epoxy coating without biochar (left) coated on the tinplate in Comparative Example 2 of the present application and the biochar coating (right) of Example 1 after bending;
[0035] Figure 4 Water contact angle photo of the water-based epoxy coating without biochar (left) of Comparative Example 2, the wheat biochar coating (middle) of Example 4, and the wood biochar coating (right) of Example 1;
[0036] Figure 5Physical pictures of uncoated iron of Comparative Example 1, waterborne epoxy coating without biochar of Comparative Example 2 and biochar coating of Example 1 before and after electrochemical test;
[0037] Figure 6 Polarization curves of electrochemical test of uncoated iron of Comparative Example 1, waterborne epoxy coating without biochar of Comparative Example 2 and wood, wheat, corn and rice biochar coating of Example 1, 4, 5, 6 (left) and waterborne epoxy coating without biochar of Comparative Example 4 prepared under 45℃ ultrasonic temperature treatment and wood, wheat, corn and rice biochar coating of Example 2, 7, 8, 9 (right);
[0038] Figure 7 Physical pictures of coating prepared by single waterborne epoxy resin containing 10 parts of biochar of Example 3 (left), single waterborne polyurethane containing biochar of Comparative Example 3 (middle) and biochar-epoxy-polyurethane mixed waterborne resin of Example 10 (right);
[0039] Figure 8 Water absorption test results of waterborne epoxy coating without biochar of Comparative Example 2, 20 parts of biochar waterborne coating of Example 1 and 10 parts of biochar waterborne coating of Example 3;
[0040] Figure 9 Coating hardness test results of waterborne epoxy coating without biochar of Comparative Example 2 (i.e. 0 parts of biochar), 10, 20, 30, 40 parts of wheat biochar waterborne coating of Example 4 and Example 13 dried for 4 days. DETAILED DESCRIPTION
[0041] The present application will be further described in detail as follows.
[0042] Example 1
[0043] The preparation method of the biochar marine anticorrosive waterborne coating comprises the following steps:
[0044] (1) Carbonize wood at a temperature of 400℃ to obtain wood biochar, take 20 parts of wood biochar by mass, add the wood biochar into 64 parts of waterborne epoxy resin, uniformly stir, add 0.2 parts of dispersant, and then put into normal temperature water for ultrasonic dispersion and stirring; wherein, the dispersant is model SN-5040, a polycarboxylic acid sodium salt type dispersant;
[0045] (2) Add 16 parts of curing agent, slowly keep stirring in the same direction; wherein, the curing agent is model F0705, a water-soluble epoxy curing agent of polyamide type;
[0046] (3) Add 0.3 parts of water-based defoaming agent and 0.2 parts of coupling agent to the above solution drop by drop; wherein the water-based defoaming agent is model J0413, a non-ionic water-based defoaming agent; the coupling agent is model KH-560;
[0047] (4) Put the paint solution into normal temperature water for ultrasonic dispersion, continue to stir, and defoaming treatment;
[0048] (5) Add 0.5 parts of thickening agent and 0.1 parts of drying accelerator to the above solution drop by drop, stir uniformly, and finally obtain 20 parts of biochar water-based coating solution; wherein the thickening agent is model J0604, a polyether type polyurethane water-based emulsion thickening agent; the drying accelerator is model J2503, a water-based composite type cobalt-free drying accelerator.
[0049] The application also provides the application of the above-mentioned biochar marine corrosion prevention water-based coating, which comprises the following steps:
[0050] (1) Polish the surface of the tinplate sheet (size: 120mm*5mm*0.3mm) with 600# and 800# sandpaper respectively to remove the passivation layer, wipe the surface with anhydrous ethanol, perform ultrasonic cleaning in deionized water, and place in a vacuum oven for drying for use.
[0051] (2) Grind pure iron (size: 10mm*10mm*0.3mm) using silicon carbide sandpaper with particle sizes of 400, 800 and 1200, perform ultrasonic cleaning with anhydrous ethanol and deionized water, wipe the surface water stains with dust-free paper, and dry for use. Strip about 5mm of the exposed copper wire at one end of the wire, use carbon conductive tape to bond the copper wire to one side of the treated pure iron, apply two-component copper conductive adhesive to ensure conductivity, and dry in a 60℃ oven for 2h. Use double-sided tape to bond the other side of the pure iron, i.e. the working surface, to a circular mold, mix the metallographic epoxy resin and the curing agent in a weight ratio of 2:1, stir in the same direction for 2-3min, and pour into the mold after fully mixing to submerge the sample. After the epoxy glue is cured, remove the double-sided tape, and grind the working surface of the pure iron with sandpaper with particle sizes of 400, 800 and 1200 in sequence. Clean and degrease the sample with deionized water and anhydrous ethanol, and dry to obtain an electrochemical test working electrode sample, which is placed in a vacuum bag for use.
[0052] Use a coater to take the biochar water-based coating solution prepared in Example 1, and scrape it onto the tinplate sheet, which is placed in standard conditions (temperature 23±2℃, relative humidity 50±10%) for 96h, then placed in a 40±2℃ oven for 48h, and finally placed in standard conditions for 4h. Similarly, use a coater to take the biochar water-based coating solution, and scrape it onto the electrochemical test working electrode, which is dried in standard conditions for 1d, and then placed in a 40±2℃ oven for 1d.
[0053] Example 2
[0054] The steps are the same as those in Example 1, except that during the ultrasonic treatment in water in step (1), the water temperature is 45°C.
[0055] Example 3
[0056] The steps were the same as in Example 1, except that the following three groups of experiments were set up regarding the proportions of biochar, waterborne epoxy resin, and curing agent:
[0057] 10 parts of biochar water-based coating liquid includes: 10 parts of biochar, 72 parts of water-based epoxy resin, and 18 parts of curing agent;
[0058] 30 parts of biochar water-based coating liquid includes: 30 parts of biochar, 56 parts of water-based epoxy resin, and 14 parts of curing agent;
[0059] 40 parts of biochar water-based coating liquid include: 40 parts of biochar, 48 parts of water-based epoxy resin, and 12 parts of curing agent.
[0060] Example 4
[0061] The steps are the same as those in Example 1, except that the biochar raw material is wheat.
[0062] Example 5
[0063] The steps are the same as those in Example 1, except that the biochar raw material is corn.
[0064] Example 6
[0065] The steps are the same as those in Example 1, except that the raw material of biochar is rice.
[0066] Example 7
[0067] The steps are the same as those in Example 2, except that the biochar raw material is wheat.
[0068] Example 8
[0069] The steps are the same as those in Example 2, except that the biochar raw material is corn.
[0070] Example 9
[0071] The steps are the same as those in Example 2, except that the biochar raw material is rice.
[0072] Example 10
[0073] (1) Weigh 20 parts of biochar and add them to 32 parts of water-based epoxy resin, stir evenly, add dispersant, and put the water-based epoxy solution containing biochar into water for ultrasonic dispersion and stirring;
[0074] (2) adding 40 parts of aqueous polyurethane, and adding defoamer and coupling agent dropwise to the above solution;
[0075] (3) The paint solution is put into normal temperature water for ultrasonic dispersion;
[0076] (4) Continue to stir to add 8 parts of curing agent, and degassing treatment defoaming, finally get biochar water-based coating liquid.
[0077] Example 11
[0078] The procedure is the same as Example 10, except that the order of addition of the water-based epoxy resin, biochar, and water-based polyurethane is changed: the water-based epoxy resin and water-based polyurethane are mixed first, and then the biochar is added.
[0079] Example 12
[0080] The procedure is the same as Example 10, except that the order of addition of the water-based epoxy resin, biochar, and water-based polyurethane is changed: the biochar is first added to the water-based polyurethane, and then the water-based epoxy resin is added.
[0081] Example 13
[0082] The procedure is the same as Example 3, except that the biochar raw material is wheat.
[0083] Example 14
[0084] The procedure is the same as Example 1, except that in step (1), the temperature for preparing the biochar is 500°C.
[0085] Example 15
[0086] The procedure is the same as Example 1, except that the order of addition of the water-based epoxy resin, biochar, and curing agent is changed: the water-based epoxy resin and curing agent are mixed first, and then the biochar is added.
[0087] Example 16
[0088] The procedure is the same as Example 1, except that the order of addition of the water-based epoxy resin, biochar, and curing agent is changed: the curing agent is first diluted and added to the biochar, and then the water-based epoxy resin is added.
[0089] Comparative Example 1
[0090] Unlike Example 1, no paint is applied to the iron sheet.
[0091] Comparative Example 2
[0092] Unlike Example 1, no wooden biochar is added in step (1). Then the iron sheet is coated with a water-based epoxy resin coating that does not contain biochar.
[0093] Comparative Example 3
[0094] Different from example 10, no waterborne epoxy resin was added in step (1), and no curing agent was added in step (4), so that the iron sheet was coated with a single waterborne polyurethane coating containing biochar.
[0095] Comparative example 4
[0096] Different from example 2, no wood biochar was added in step (1). So that the iron sheet was coated with a waterborne epoxy resin coating without biochar treated at an ultrasonic temperature of 45℃.
[0097] The raw materials used in the above examples are all commercially available products, among which the biochar is purchased from Henan Housen Environmental Protection Technology Co., Ltd., the waterborne resin and the auxiliary agent are purchased from Shenzhen Jitian Chemical Co., Ltd., the tinplate sheet is purchased from Shanghai Qise Trading Co., Ltd., and the pure iron is purchased from Jiyu Scientific Metal. The anhydrous ethanol (99.5%) and sodium chloride (%) are purchased from Macklin Company. The deionized water used in the experiment is produced by using an ultrapure water machine.
[0098] Corrosion resistance test
[0099] The water absorption rate of the coating was obtained by monitoring the weight of the coating immersed in water for one hundred days.
[0100] The corrosion resistance of the coating was tested by electrochemical test method.
[0101] Basic properties of the coating
[0102] The static contact angle of a 3 μL water droplet was measured on a contact angle measuring instrument, and the average water contact angle was obtained by measuring 3 regions of the same coating.
[0103] The hardness of the coating was tested by a Shore hardness tester, and the average hardness value was obtained by measuring 5 regions of the same sample.
[0104] Figure 1 The flow chart of the preparation method of the present application.
[0105] Figure 2 The wood biochar coating of example 1 and example 3 in the present application is shown in the figure from left to right, with the biochar content being 10 parts, 20 parts, 30 parts and 40 parts respectively; it can be seen that the biochar as a filler is well dispersed in the waterborne epoxy resin, and the integration amount can reach 40 parts.
[0106] Figure 3 The waterborne epoxy coating without biochar coated on tinplate in comparative example 2 (left) and the biochar coating in example 1 (right) are shown in the figure after bending; it can be seen that the waterborne epoxy coating is prone to form shrinkage holes when solidifying, and the formed coating is uneven; while the biochar coating is dense and uniform on the surface.
[0107] Figure 4In the figure, the left picture is the water contact angle picture of the waterborne epoxy coating without biochar of Comparative Example 2, the middle picture is the water contact angle picture of the wheat biochar coating of Example 4, and the right picture is the water contact angle picture of the wood biochar coating of Example 1. It can be seen that the waterborne epoxy coating is in a hydrophilic state, and the addition of biochar increases the water contact angle of the coating. The wheat and wood biochar coatings reach a slightly hydrophobic state, but the average water contact angle of the wood biochar coating is 106.2, which is slightly larger than that of the wheat biochar coating of 103.2, indicating that the wood biochar coating has better hydrophobicity.
[0108] Figure 5 In the figure, the left picture is the water contact angle picture of the waterborne epoxy coating without biochar of Comparative Example 2, the middle picture is the water contact angle picture of the wheat biochar coating of Example 4, and the right picture is the water contact angle picture of the wood biochar coating of Example 1. It can be seen that the waterborne epoxy coating is in a hydrophilic state, and the addition of biochar increases the water contact angle of the coating. The wheat and wood biochar coatings reach a slightly hydrophobic state, but the average water contact angle of the wood biochar coating is 106.2, which is slightly larger than that of the wheat biochar coating of 103.2, indicating that the wood biochar coating has better hydrophobicity.
[0109] Figure 6 In the figure, the left picture is the water contact angle picture of the waterborne epoxy coating without biochar of Comparative Example 2, the middle picture is the water contact angle picture of the wheat biochar coating of Example 4, and the right picture is the water contact angle picture of the wood biochar coating of Example 1. It can be seen that the waterborne epoxy coating is in a hydrophilic state, and the addition of biochar increases the water contact angle of the coating. The wheat and wood biochar coatings reach a slightly hydrophobic state, but the average water contact angle of the wood biochar coating is 106.2, which is slightly larger than that of the wheat biochar coating of 103.2, indicating that the wood biochar coating has better hydrophobicity.
[0110] Figure 7 In the figure, the left picture is the water contact angle picture of the waterborne epoxy coating without biochar of Comparative Example 2, the middle picture is the water contact angle picture of the wheat biochar coating of Example 4, and the right picture is the water contact angle picture of the wood biochar coating of Example 1. It can be seen that the waterborne epoxy coating is in a hydrophilic state, and the addition of biochar increases the water contact angle of the coating. The wheat and wood biochar coatings reach a slightly hydrophobic state, but the average water contact angle of the wood biochar coating is 106.2, which is slightly larger than that of the wheat biochar coating of 103.2, indicating that the wood biochar coating has better hydrophobicity.
[0111] Figure 8The water absorption test results of Comparative Example 2 (waterborne epoxy coating without biochar), Example 1 (20 parts of biochar waterborne coating), and Example 3 (10 parts of biochar waterborne coating) show that the water absorption rate of the biochar coating is higher than that of the waterborne epoxy coating in the first 30 days, and the water absorption rate curve of the biochar coating tends to be flat after 30 days, and the water absorption rate is lower than that of the waterborne epoxy coating.
[0112] Figure 9 The coating hardness test results of Comparative Example 2 (waterborne epoxy coating without biochar, i.e., 0 parts of biochar), Example 4, and Example 13 (10, 20, 30, 40 parts of biochar coating) dried for 4 days show that the addition of biochar significantly improves the hardness of the waterborne coating, and the hardness of the front and back surfaces of the coating is similar when the amount of biochar is 10 parts and 30 parts.
[0113] Table 1
[0114] Point 1 Point 2 Point 3 Point 4 Point 5 Average 1 65 66 72 65 68 67.2 2 100 100 98 99 100 99.4 3 58 62 64 62 57 60.6 4 50 52 48 52 51 50.6 5 48 47 45 51 49 48
[0115] Note: In the table, points 1, 2, 3, 4, and 5 are the hardness measured at five different points on the surface of the coating.
[0116] Table 1 is the coating hardness test data after drying for 4 days, which includes 10 parts of biochar epoxy coating of Example 3 (①), single waterborne polyurethane coating containing biochar of Comparative Example 3 (②), and biochar-epoxy-polyurethane waterborne coating of Example 10 (③), epoxy-polyurethane-biochar waterborne coating of Example 11 (⑤), and biochar-polyurethane-epoxy waterborne coating of Example 12 (④). It can be seen that the average hardness of the single waterborne polyurethane coating containing biochar (②) is the highest, but the hardness of the coating is not the best. Figure 7 (middle) reflects that its ductility is very poor. Although the hardness of the coating obtained by mixing resins decreases, the ductility is greatly improved. However, the change in the preparation sequence of the coating also affects the hardness of the coating. The hardness value of Example 10 (③) is greater than that of Example 12 (④), and the hardness value of Example 11 (⑤) is similar to that of Example 12 (④).
Claims
1. A biochar marine anti-corrosion water-based paint, characterized in that: Comprising component A and component B; The component A and the component B are mixed to form the biochar marine anti-corrosion water-based coating; The component A comprises, by mass, 10-40 parts of biochar, 24-72 parts of water-based epoxy resin, and 0.1-0.4 parts of dispersant; the component B comprises, by mass, 6-18 parts of curing agent, 0.15-0.6 parts of water-based defoaming agent, 0.25-1 parts of thickener, 0.1-0.4 parts of coupling agent, and 0.05-0.2 parts of drying agent.
2. The biochar marine anti-corrosion water-based paint according to claim 1, characterized in that: The component A further comprises waterborne polyurethane and / or waterborne acrylic resin.
3. The biochar marine anticorrosive water-based paint according to claim 1, characterized in that: The mass ratio of the waterborne epoxy resin to the waterborne polyurethane or waterborne acrylic resin is 1:1-2:1; the ratio of the mass of the waterborne epoxy resin to the sum of the masses of the waterborne polyurethane and the waterborne acrylic resin is 1:1-2:
1.
4. The biochar marine anticorrosive water-based paint according to claim 1, characterized in that: The biochar is sourced from one of wheat, corn, rice or wood.
5. A method for preparing the biochar marine anticorrosive water-based coating according to claim 1, characterized in that: The following steps are involved: (1) Mixing biochar, water-based epoxy resin, dispersant, curing agent, and water-based defoamer, and performing ultrasonic dispersion; (2) adding a coupling agent to step (1) to obtain a coating solution; (3) ultrasonically dispersing the coating solution and degassing and defoaming the coating solution; (4) Add a thickener and a drying agent to step (3) and stir evenly to obtain a biochar marine anti-corrosion water-based coating.
6. The method for preparing the biochar marine anticorrosive water-based coating according to claim 5, characterized in that: In step (3), the temperature of ultrasonic dispersion is 35-45°C.
7. The method for preparing the biochar marine anticorrosive water-based coating according to claim 5, characterized in that: In step (1), the biochar is mixed with the water-based epoxy resin and then a dispersant, a curing agent, and a water-based defoaming agent are added in sequence; Alternatively, a defoamer is added after mixing the waterborne epoxy resin with the curing agent, followed by ultrasonic dispersion, and then biochar and a dispersant are added in sequence; Alternatively, the curing agent is diluted and mixed with the biochar, and then a dispersant is added and ultrasonically dispersed, and then the water-based epoxy resin is added and stirred.
8. The method for preparing the biochar marine anticorrosive water-based coating according to claim 1, characterized in that: In step (1), the biomass is carbonized at a temperature of 400 to 500° C. to obtain biochar.
9. The method for preparing the biochar marine anticorrosive water-based coating according to claim 2, characterized in that: The following steps are involved: (1) mixing biochar, water-based epoxy resin, water-based polyurethane and / or water-based acrylic resin, a dispersant, a water-based defoaming agent, and a coupling agent, and performing ultrasonic dispersion; (2) adding a curing agent to step (1), and degassing and defoaming; (3) Add a thickener and a drying agent to step (2) and stir evenly to obtain a biochar marine anti-corrosion water-based coating.
10. The method for preparing the biochar marine anticorrosive water-based coating according to claim 9, characterized in that: In step (1), the biochar and the water-based epoxy resin are mixed and stirred, a dispersant is added, and then water-based polyurethane and / or water-based acrylic resin, a water-based defoaming agent, and a coupling agent are added in sequence; Alternatively, the biochar is mixed with water-based polyurethane and / or water-based acrylic resin, a dispersant is added, and then a water-based epoxy resin, a water-based defoamer, and a coupling agent are added in sequence; Alternatively, a water-based epoxy resin is mixed with a water-based polyurethane and / or a water-based acrylic resin, a defoamer is added, and then biochar and a dispersant are added in sequence; the water-based defoamer and coupling agent are added after the curing agent is added in step (2).
Citation Information
Patent Citations
Graphene anticorrosive coating, production process thereof and heat collector coated with coating
CN110183938A
Anticorrosive paint for explosion-proof lamps and preparation process thereof
CN111218192A
Anticorrosive weather-resistant functional integrated water-based graphene coating and preparation method thereof
CN111378346A
Biochar nanoparticle modified epoxy zinc-rich coating and preparation method thereof
CN112961573A
Graphene modified waterborne epoxy anticorrosive paint and preparation method thereof
CN114231120A
Cited By
Plant-based inorganic coating and preparation method thereof
CN121362476A